2014
DOI: 10.1007/s00125-014-3428-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-centre study of 628 adult, primary kidney transplant recipients showing no unfavourable effect of new-onset diabetes after transplant

Abstract: Less-than-expected post-NODAT risk for graft loss and death may exist in the current climate of tighter glucose monitoring post transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
3
17
2
Order By: Relevance
“…PTDM risk factors like elevated BMI and older age have also become more prevalent among wait‐listed patients . Perhaps, in part, because of these changes, recent studies have not uniformly demonstrated different patient and allograft outcomes in recipients with PTDM compared to those without diabetes in the United States . In contrast, a Norwegian single‐center study reported an independent association between PTDM and patient survival, but not with allograft survival; however, 90% of patients in this study were receiving cyclosporine A‐based immunosuppression .…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…PTDM risk factors like elevated BMI and older age have also become more prevalent among wait‐listed patients . Perhaps, in part, because of these changes, recent studies have not uniformly demonstrated different patient and allograft outcomes in recipients with PTDM compared to those without diabetes in the United States . In contrast, a Norwegian single‐center study reported an independent association between PTDM and patient survival, but not with allograft survival; however, 90% of patients in this study were receiving cyclosporine A‐based immunosuppression .…”
Section: Introductioncontrasting
confidence: 60%
“…A detrimental effect of PTDM on patient survival has been previously reported . However, the three most recently published studies from the United States have not detected independent associations between PTDM and either allograft survival, all‐cause mortality, or DWFG . It has been speculated that these negative findings may have been due to the enrollment of only patients transplanted after the year 2000 when greater awareness and pro‐active treatment of PTDM may have reduced the consequences of this disease (the study by Pirsch et al .…”
Section: Discussionmentioning
confidence: 99%
“…We found no relationship between perioperative glycaemia and AR, supporting the supremacy of preventing rejection rather than modifying diabetogenic immunosuppressant regimens as the primary strategy to prevent PTDM [18]. Although PTDM has been associated with poorer outcomes in early studies [1], our results at 12 months are consistent with more recent findings that outcomes of those with PTDM are similar to those without diabetes [19, 20], although this is limited by short follow-up and small numbers.…”
Section: Discussionsupporting
confidence: 87%
“…22 Current investigations indeed have pointed toward a reduced risk of NODAT on major adverse events, presumably due to more thorough blood glucose monitoring posttransplant. 23,24 In line with these more recent reports, our data could not determine any association of prediabetes with reduced transplant function or graft and patient outcomes. Hyperglycemia as caused by overt diabetes can lead to insulin resistance, dyslipidemia, platelet activation, or hypertension.…”
Section: Discussionsupporting
confidence: 71%